+0  
 
0
79
3
avatar

Evaluate $(a^b)^a - (b^a)^b$ for $a = 2$ and $b = 3$.

 Jul 2, 2021
 #1
avatar
0

Substitute both numbers in ===> (2^3)^2 - (3^2)^3 = 2^6 - 3^6 = -665

 Jul 2, 2021
 #2
avatar+336 
+4

Hey there, Guest!

 

So, the equation is \(\left(a^b\right)^a-\left(b^a\right)^b\ \) and we'll substitute properly.

 

\(\left(2^3\right)^2-\left(3^2\right)^3\)

 

\(8^2−(3^2)^3\)

 

\(64−(3^2)^3\)

 

\(64−9^3\)

 

\(64−729\)

 

−665

 

Hope this helped! :)

( ゚д゚)つ Bye

 Jul 2, 2021
 #3
avatar+20 
+1

This equals (2^3)^2 - (3^2)^3 = 2^6 - 3^6 = 64 - 729 = -665. 

 Jul 2, 2021

19 Online Users